Quantification of the development trend of results during the career of Croatian sprinters in the 50m freestyle concerning the best European swimmers: Initial age-performance model - Šiljeg, K.; Dopsaj, M. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The aim of this research is to compare the legality of Age-Trend changes in the development of results during the career of top European (EU) and Croatian (CRO) sprinter swimmers in the 50m crawl technique. The obtained results show an insight into the characteristics and diversity of the applied technology of training work in both systems. The paper used the results of current age and annual peak performance in a 50-meter pool for a sample of 24 male and 21 female swimmers (EU = 16 male and 15 female swimmers; CRO = 9 male and 7 female swimmers). Two variables were used for the analysis: 1) current age, and 2) the best result in the 50m crawl swum in a given calendar year. A career performance trajectory was calculated using the polynomial equation for each swimmer. The results showed that there is an evident quantitative difference between Croatians and European swimmers, which is dominantly related to the following: European crawl male sprinters and female sprinters during their careers reach their career peak at a later age (about 2 and 4 years later for men and women, respectively). The reached peak result is better for men by 0.74 sec. (3.26%), and for women by 1.81 sec. (6.73%). In addition, the career of European swimmers lasts on average 5 to 6 years longer. The results point to the conclusion that crawl-sprint swimming among women in Croatia is at a lower level of development and is systemically more endangered compared to men.